Prescribing patterns of benzodiazepine in Malaysia from 2014 to 2016 - Ab Rahman, Norny Syafinaz; Pakururazi, Fatin Azzyati; Zin, Che Suraya; Abdul Halim, Helina (Wiley, 2018)
Background: Although benzodiazepines (BZDs) are often prescribed to treat wide range of psychiatric and neurological conditions, they are also associated with various harms and risks, as well as tendency of inappropriate prescribing. To date, the prescribing patterns of BZDs at outpatient tertiary hospital in Malaysia are still scarce. Objectives: To examine the patterns of BZDs prescribing at outpatient tertiary hospital in Malaysia. Methods: A cross‐sectional retrospective study was conducted from January 2014 to December 2016 using the prescriptions received by the outpatient pharmacy of tertiary hospital. Prescriptions with any seven types of BZDs (alprazolam, bromazepam, clobazam, diazepam, clonazepam, loraxepam, and midazolam) were identified and included in this study. Information on patients' age and gender, prescription date, drug name, dosage, frequency, duration, quantity supplied, and prescriber's name were extracted from the prescriptions. Only prescrip- tions for patients' age of 18 and above were included in this study. Total number of prescriptions with BZDs, total number of patients received BZDs, and total number of each type of BZDs were measured yearly and over 3 years. Data were analyzed descriptively using Stata v13. Results: A total of 5711 BZDs prescriptions were issued (n = 1959, n = 2051, and n = 1701 for year 2014, 2015, and 2016, respectively) from January 2014 to December 2016. BZDs were prescribed for 1947 patients (n = 895 in year 2014, n = 934 in 2015, and n = 782 in 2016). Alprazolam (39.7%, n = 3542) was the most frequently pre- scribed followed by lorazepam (21.1%, n = 1880), diazepam (20.7%, n = 1851), clonazepam (17.1%, n = 1530), and less than 1% to other BZDs. Sixty percent (n = 5422) of patient were prescribed with short‐acting BZDs, 21.6% (n = 1928) intermediate‐acting BZDs and 17.1% (n = 1530) long acting BZDs. Majority (90.7%, n = 5015) of BZDs prescription were for psychiatric disorders, in which, higher per- centage (82.3%) of BZDs were prescribed as anxiolytics followed by 17.1% as hypnotics. Among all BZDs, alprazolam, and lorazepam showed decreasing pattern over 3 years period. Conclusions: Short‐acting BZDs (alprazolam and lorazepam) were highly prescribed at the outpatient tertiary hospital in Malaysia. The main indication of the BZDs was as anti‐anxiety. However, data avail- able were from the prescriptions only. Thus, further research is required to examine the use of BZDs at patient‐level.